High N2O5 Concentrations Observed in Urban Beijing: Implications of a Large Nitrate Formation Pathway - Wang, H. C.; Lu, K. D.; Chen, X. R.; Zhu, Q. D.; Q. Chen; Guo, S.; Jiang, M. Q.; X. Li; Shang, D. J.; Tan, Z. F.; Y.S. Wu; ZJ Wu; et al. (Environmental Science & Technology Letters, 2017)
The heterogeneous hydrolysis of dinitrogen pentoxide (N2O5) is important to understanding the formation of particulate nitrate (pNO(3)(-)). Measurements of N2O5 in the surface layer taken at an urban site in Beijing are presented here. N2O5 was observed with large day-to-day variability. High N2O5 concentrations were determined during pollution episodes with the co-presence of large aerosol loads. The maximum value was 1.3 ppbv (5 s average), associated with an air mass characterized by a high level of O-3. N2O5 uptake coefficients were estimated to be in the range of 0.025-0.072 using the steady-state lifetime method. As a consequence, the nocturnal pNO(3)(-) formation potential by N2O5 heterogeneous uptake was calculated to be 24-85 mu g m(-3) per night and, on average, 57 mu g m(-3) during days with pollution. This was comparable to or even higher than that formed by the partitioning of HNO3. The results highlight that N2O5 heterogeneous hydrolysis is vital in pNO(3)(-) formation in Beijing.
Keywords: air-quality; boundary-layer; chemistry; China; haze; model simulation; nitryl chloride; no3; pm2.5; rural site